GANGGUAN PERTUMBUHAN DAN PERKEMBANGAN PADA ANAK USIA 0,5-1,9 TAHUN TERKAIT DENGAN ASUPAN MAKANAN DAN PENGASUHAN YANG KURANG - Harahap, Heryudarini; Budiman, Basuki; Widodo, Yekti (GIZI INDONESIA, 2018)
Growth and development of children affected by various risk factors include malnutrition, poverty, and a less stimulated home environment. The objective of this analysis was to calculate the proportion of growth and development disorder and to determine the association of food intake and care for children with children’s growth and development. Samples were 247 children aged of 0.5-1.9 years who participated in the South East Asian Nutrition Survey (SEANUTS) in 2011. Growth was assesed by height for age in Z-score of WHO standard. Development was measured using Denver II test. Children were divided into four groups: 1).normal height with normal development (NH-ND); 2).stunting with normal development (S-ND), 3).normal height with suspected underdevelopment (NH-SD), and 4).stunting with suspected underdevelopment (S-SD). Protein intake was divided into adequate (≥80% RDA) and inadequate (<80% RDA). Care for children was measured by the length of carrying them, categorized into ≤2 hours or >2 hours. Socio-economic status was categorized into low and high based on quintile. Age was categorized into 0.5–0.9 years and 1.0–1.9 years. Data analysis employed multi-nomial logistic regression. Proportions of NH-SD, S-ND, NH-SD and S-SD were 53.6%, 17.9%, 19.4%, and 9.1%, respectively. S-ND was associated with protein intake (OR=2.2;95%CI:1.1-4.6), aged 1.0–1.9 years (OR=6.9: 95%CI:2.2-22.1). NH-SD was associated with aged 1–1.9 years (OR=0.3; 95%CI:0.1-0.6). S-SD was associated with inadequate protein intake (OR=3.1; 95%CI:1.2-8.2), low SES and duration of carrying them more than 2 hours (OR=6.9; 95%CI:2.5-19.0). Protein intake, SES and care for children were risk factors for growth and development of children.ABSTRAKPertumbuhan dan perkembangan anak dipengaruhi oleh berbagai faktor risiko diantaranya kekurangan gizi, kemiskinan, dan lingkungan rumah yang kurang stimulasi. Tujuan analisis adalah mengetahui proporsi gangguan pertumbuhan dan perkembangan dan mempelajari asosiasi asupan makanan dan pengasuhan dengan pertumbuhan dan perkembangan anak. Sampel adalah 247 anak, berusia 0,5–1,9 tahun dari penelitian South East Asian Nutrition Study tahun 2011. Pertumbuhan dinilai melalui Z-skor tinggi badan (TB) menurut umur standar WHO. Perkembangan diukur menggunakan test Denver II. Anak dikelompokkan menjadi: 1).TB dan perkembangan normal (NH-ND), 2).stunting tetapi perkembangan normal (S-ND), 3).TB normal tetapi perkembangan terganggu (NH-SD), dan 4). stunting dan perkembangan terganggu (S-SD). Asupan protein dikelompokkan atas cukup (≥80% RDA) dan kurang (<80% RDA). Pengasuhan diukur dari lama anak digendong, dikelompokkan menjadi ≤2 jam atau >2 jam. Status sosial ekonomi dikategorikan menjadi rendah dan tinggi. Analisis yang digunakan adalah multi-nomial logistic regression. Proporsi NH-ND, S-ND, NH-SD dan S-SD berturut-turut adalah 53,6%, 17,9%, 19,4%, dan 9,1%. S-ND berhubungan dengan kurang asupan protein (OR=2,2;95%CI:1,1-4,6), umur 1–1,9 tahun (OR=6,9: 95%CI:2,2-22,1). NH-SD berhubungan dengan umur 1,0–1,9 tahun (OR=0,3; 95%CI:0,1-0,6). S-SD berhubungan dengan kurang asupan protein (OR=3,1; 95%CI:1,2-8,2), SES rendah dan anak digendong > 2 jam (OR=6,9; 95%CI:2,5-19,0). Asupan protein, sosial ekonomi status dan pengasuhan anak merupakan faktor risiko untuk terjadinya pertumbuhan dan hambatan perkembangan pada anak.Kata kunci: konsumsi makanan, pengasuhan anak, perkembangan anak, status gizi